A new species of Rudolfina Roháček, 1987 (Diptera, Sphaeroceridae) from North-east China, with key to the known Holarctic species of Rudolfina. (2nd October 2017) - Su, Lixin; Xu, Jie; Cong, Guoyi
Abstract: The present study describes a novel species of Sphaeroceridae: Limosininae (Diptera), Rudolfina zhangi Su sp. nov. (male only), R. zhangi seems to be most closely related to the European species R. rozkosnyi, on the basis of morphological characters. A key to the known Holarctic species of Rudolfina is given and Rudolfina phylogenetic relationships are discussed. Type specimens of R. zhangi have been deposited with Liaoning Key Laboratory of Urban Integrated Pest Management and Ecological Security, Shenyang University, Shenyang, Liaoning, China. http://www.zoobank.org/urn:lsid:zoobank.org:pub:3333B44F-F9E8-427C-A592-D517C28D5FE8